Effect of Octacalcium Phosphate on Osteogenic Differentiation of Induced Pluripotent Stem Cells in a 3D Hybrid Spheroid Culture - Yuki Sugai; Ryo Hamai; Yukari Shiwaku; Takahisa Anada; Kaori Tsuchiya; Tai Kimura; Manami Tadano; Kensuke Yamauchi; Tetsu Takahashi; Hiroshi Egusa; Osamu Suzuki (Biomimetics)
Octacalcium phosphate (OCP) has been shown to exhibit an osteogenic property and, therefore, has been utilized recently as a bone substitute, clinically. However, the stimulatory capacity for induced pluripotent stem (iPS) cells is not known. This study investigated whether OCP enhances osteoblastic differentiation of three-dimensionally cultured spheroids of iPS cells compared to hydroxyapatite (HA) and β-tricalcium phosphate (β-TCP). Mouse iPS cells were mixed with smaller (less than 53 μm) or larger (300–500 μm) sizes of calcium phosphate (CaP) granules and cultured in a laboratory-developed oxygen-permeable culture chip under minimizing hypoxia for up to 21 days. Osteoblastic differentiation was estimated by the cellular alkaline phosphatase (ALP) activities. The degree of supersaturation (DS) with respect to CaP phases was determined from the media chemical compositions. Incubated CaP materials were characterized by Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). The culture promoted well the formation of hybrid spheroids of CaP materials and iPS cells regardless of the type of materials and their granule sizes. The ALP activity of OCP was about 1.5 times higher than that of β-TCP and HA in smaller granule sizes. FTIR, XRD, and DS analyses showed that larger OCP granules tended to hydrolyze to HA slightly faster than smaller granules with time while HA and β-TCP materials tended to remain unchanged. In conclusion, the results suggest that OCP enhances the osteogenic differentiation of iPS cells more than HA and β-TCP through a mechanism of hydrolyzing to HA. This inherent material property of OCP is essential for enhancing the osteoblastic differentiation of iPS cells.